Perkecambahan benih dan pertumbuhan bibit jarak pagar (Jatropha curcas Linn.) dengan invigorasi menggunakan zat pengatur tumbuh pada periode simpan yang berbeda - Indah Puspitaningtyas; Syaiful Anwar; Karno Karno (Department of Agriculture, Animal and Agricultural Sciences, Diponegoro University, Semara, 2018)
Jatropha curcas is a plant that is used as an alternative energy for fossil fuel replacement because of it’s high oil content. Jatropha curcas seeds have 30-40% oil content. The purpose of the study was to improve the seed quality and to enhance seedling growth of Jatropha curcas after storage using plant growth regulator. This study used factorial design based on Completely Randomized Design with two factors and 3 replications. The first factor was seed storage which consist of 2 levels : A1 = seed storage in 2015, A2 = seed storage in 2016. The second factor was plant growth regulator level which consists of 6 levels : B1=GA+NAA 0 ppm, B2= GA+NAA 20 ppm, B3= GA+ NAA 40 ppm, B4= GA+NAA 60 ppm, B5 = GA+NAA 80 PPM, B6 = GA+NAA 100 ppm. Parameters measured were seed germination, vigor index, growth rate, plant height and the number of leaves. The data were analyzed statistically by analysis of variance and followed by Tukey test and Polynomial Orthogonal. The result showed that seed germination, vigor index and growth rate were significantly affected by storage treatment and invigoration using plant growth regulator treatment. Invigoration using auxin and gibberellic acid 40 ppm has the highest result of seed germination, vigor index and growth rate. There was no influence of seed storage and invigoration with plant growth regulator treatment on plant height and number of leaves. Keywords : Jatropha curcas, invigoration, plant growth regulator.